Antecedents and Consequences of Trust and Loyalty in Physical Banks Affecting Mobile Payments - Bo-Chiuan Su (MDPI AG, 2021)
The way of payment has changed in recent years: people have turned away from physical payment methods to virtual payment methods. The traditional banking industry is facing challenges brought by new technologies. The main purpose of this study is to investigate customer trust and loyalty transferring from physical banks to mobile payments because mobile payment platforms are a self-service technology. The goal is to create an eco-platform to facilitate transition from a cash-based economy to a cashless economy. This study is the first attempt to integrate platform management, electronic marketing (online trust and online loyalty), and relationship marketing (offline trust and offline loyalty) into one model. We theoretically and empirically take certain factors into consideration to further explore the transfer impact of physical to mobile payments, which is not discussed in literature. The SEM (structural equation modelling) analysis from the 353 respondents in this study found that trust from both the physical and mobile contexts has positively influenced loyalty. Additionally, customers’ trust and loyalty transfer from the physical to the mobile environment has had a significantly positive effect between the physical and mobile environment. Corporate reputation and structure assurance have also significantly positively affected physical trust and mobile trust, respectively. The findings also reveal that the structure assurance plays an essential role in mobile payment. Users may have certain concerns about the procedure of transactions and their personal information. Theoretical and practical implications are provided.